Investigation into sand mura effects of a-IGZO TFT LCDs. (August 2016) - Liu, Xiang; Hu, Hehe; Ning, Ce; Shang, Guangliang; Yang, Wei; Wang, Ke; Lu, Xinhong; Lee, Woobong; Wang, Gang; Xue, Jianshe; Jun, Jung mok; Zhang, Shengdong
Abstract: The reliability of liquid crystal display (LCD) panels based on amorphous indium-gallium-zinc oxide thin-film transistors (a-IGZO TFTs) is investigated. It is revealed that the a-IGZO TFT LCDs also have sand mura issue at high operation temperature. Analysis shows that the sand mura is caused by the positive Vth shift of the a-IGZO TFTs. To suppress the Vth shift, fabrication process of the a-IGZO TFTs is optimized with a-IGZO channel layer annealed at 300 °C and etch-stop layer deposited at 250 °C. The process optimization lessens the absorbed and non-bonded oxygen atoms in the a-IGZO channel layer and desorbed water molecules on the back channel surface. The results show that the Vth shift is significantly alleviated and the sand mura is thus effectively minimized with the optimized process. Graphical abstract: Variation of the transfer characteristics of the different fabricated a-IGZO TFTs under thermal gate bias stress of 30 V at 80 °C for 7200 s (a) initial fabrication processes, and (b) optimized fabrication processes. Highlights: The mechanism of sand mura in the a-IGZO LCD reliability relies on Vth stability of TFTs. An optimized process for improving the Vth stability of a-IGZO TFTs is proposed. The improvement of Vth stability is attributed to lessening the absorbed oxygen atoms in the a-IGZO and desorbed water molecules on the back channel surface permeated from ESL layer.